ChemInform Abstract: [Silver(I)(Pyridine‐Containing Ligand)] Complexes as Unusual Catalysts for A3‐Coupling Reactions. Issue 7 (29th January 2015) - Trose, Michael; Dell'Acqua, Monica; Pedrazzini, Tommaso; Pirovano, Valentina; Gallo, Emma; Rossi, Elisabetta; Caselli, Alessandro; Abbiati, Giorgio
Abstract The reaction of aldehydes, alkynes, and amines is best catalyzed by the shown macrocyclic silver complex.